Serological Characteristics, Etiological Analysis, and Treatment Prognosis of Children with Congenital Hypothyroidism - Lin shen; Jingchao Ding (Emergency Medicine International)
Objective. The aim of the study is to analyze the serological features, etiology, and prognosis of congenital hypothyroidism (CH) treated with L-thyroxine sodium (L-T4). Methods. A total of 126 CH children in our hospital from June 2015 to January 2020 were selected as the research objects, and L-T4 treatment was given immediately after diagnosis. After diagnosis and 24 months of treatment, laboratory serum thyroid function-related indicators were examined, and thyroid changes were determined by ultrasound. We compared serum thyroxine levels in children with different thyroid changes, compared serum thyroid hormone levels, serum ghrelin levels, and body mass index (BMI) changes in children with CH before treatment and after 24 months of treatment, and analyzed the prognosis of treatment in children. In terms of thyroid changes in 126 CH children, 32 cases (25.40%) had a normal thyroid gland, 16 cases (12.70%) had a hypoplastic thyroid gland, 40 cases (31.75%) had an ectopic thyroid gland, 28 cases (22.22%) had an absent thyroid gland, and 10 cases (7.93%) had an enlarged thyroid gland, with an ectopic thyroid gland being the most common. In terms of serological expression of CH children, the TSH level in children with thyroid dysplasia was significantly higher than that in children with basic normal and T3 and T4 levels were significantly lower than those in children with basic normal (P<0.05). At the same time, the TSH level in children with thyroid absence, ectopic, and enlargement was increased, while thyroxine (T4) and tri-iodothyronine (T3) levels were decreased compared with those in children with thyroid dysplasia. The difference was statistically significant (P<0.05). Univariate analysis showed that there were statistically significant differences in birth weight, week of gestation at delivery, maternal age at childbirth, household registration, and a family history of thyroid disease compared between the two groups (P<0.05); multivariate logistic regression analysis showed that birth weight <2,500 g, maternal age >35 years, rural residence, and a family history of thyroid disease were risk factors for neonatal CH (P<0.05). Serum thyroid-stimulating hormone (TSH) levels, serum ghrelin levels, and the body mass index of children with CH decreased significantly, and T4 levels increased significantly after 24 months of treatment (P<0.05). Conclusion. Screening for common causes of CH is conducive to timely detection of children with CH, and L-T4 treatment can effectively improve thyroid function in children.